2007
DOI: 10.1063/1.2431570
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic wave propagation in a macroscopically inhomogeneous porous medium saturated by a fluid

Abstract: The equations of motion in a macroscopically inhomogeneous porous medium saturated by a fluid are derived. As a first verification of the validity of these equations, a two-layer rigid frame porous system considered as one single porous layer with a sudden change in physical properties is studied. The wave equation is derived and solved for this system. The reflection and transmission coefficients are calculated numerically using a wave splitting-Green's function approach (WS-GF). The reflected and transmitted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 22 publications
0
43
0
Order By: Relevance
“…In an equivalent fluid medium, [17] the appropriate conservation of momentum and constitutive relations take the form: [24] being two relaxation functions given by…”
Section: Outline Of the Numerical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…In an equivalent fluid medium, [17] the appropriate conservation of momentum and constitutive relations take the form: [24] being two relaxation functions given by…”
Section: Outline Of the Numerical Proceduresmentioning
confidence: 99%
“…In [17], it is shown that the wave equation describing the propagation in a macroscopicallyinhomogeneous porous medium in the rigid frame approximation can formally take the form of the usual acoustic wave equation in a macroscopically-inhomogeneous fluid (in which the microscopic features of the porous medium are homogenized) with spatial (and frequency) dependent compressibility κ e (x, ω) and density ρ e (x, ω).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] These methods are usually simpler to implement than methods based on a Green's function approach. [11][12][13][14] The accuracy can be set to any desired level, by choosing a sufficiently large number of layers.…”
Section: A Feasibility Of Saw Elastic Depth Profilingmentioning
confidence: 99%
“…[1][2][3][4][5][6] In particular, airframe noise, which is generated through the interaction between the turbulent flow and the solid bodies on the aircraft, has been identified as an "aircraft noise barrier" since the early seventies. 7 Therefore, considering the interdisciplinary challenge between fluid mechanics and acoustics arising from this noise effect, airframe noise reduction has become a major concern for stakeholders within the aviation sector, acoustic experts, fluid mechanics engineers and researchers.…”
Section: Introductionmentioning
confidence: 99%